Pelatihan Pengembangan Media Pembelajaran Interaktif untuk Meningkatkan Literasi-Numerasi Digital Guru Sekolah Dasar di Era Merdeka Belajar - AR, Muhammad Misbahudholam; Aini, Kurratul; Sama’, Sama’; Hidayatillah, Yetti (Lembaga Peneliian dan Pengabdian Masyarakat (LPPM) Universitas Islam Madura (UIM), 2024)
Service is seen as very useful and essential in improving the conditions and quality of society. This community service activity is in collaboration with the Batuan I Elementary School located in the village and sub-district of Batuan. Strengthening literacy and numeracy is a policy of the previous curricula, which is continued and strengthened in the independent curriculum. Some of the efforts to develop numeracy literacy skills at SDN Batuan I are by providing a reading corner, literacy tree, and student arrival hours. Efforts to develop numeracy literacy skills at SDN Batuan include providing a reading corner, literacy tree, and student arrival hours. One way to do this is by utilizing information and communication technology to create interactive learning media. In this community service program, the targets are SDN Batuan I teachers who still have difficulty utilizing information and communication technology as interactive media to support learning activities. In essence, this community service program solves the problems experienced by partners through workshops to train teachers' skills in making interactive media based on information and communication technology.